The Role of Work Engagement and Work Spirit in Enhancing job Performance of Sanitation Workers in Cirebon Regency - Sucipto Sucipto; Asep Gunawan; Hevy Febriyansyah (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study examines the influence of Work Engagement and work spirit on the performance of the "Pasukan Kuning" (waste management workers) at the Environmental Agency of Cirebon Regency. Observations and interviews revealed that low work spirit and Work Engagement are the main factors contributing to the decline in their performance. A quantitative method was employed, with data collected through questionnaires from 100 respondents selected using the Slovin formula. The data were analyzed using validity tests, reliability tests, normality tests, multiple linear regression, and hypothesis testing (t-test and F-test). The results indicate that both Work Engagement and work spirit have a positive and significant impact, both partially and simultaneously, on the performance of the workers. The coefficient of determination (R²) of 80.3% suggests that these two variables are dominant in influencing performance. These findings highlight the importance of enhancing Work Engagement and work spirit through training, incentives, and managerial approaches focused on psychological well-being and motivation. This study provides practical contributions to human resource management in the sanitation sector and serves as a basis for formulating more effective policies.